2020
DOI: 10.1155/2020/8630368
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Alleviates Pain‐Related Emotion by Upregulating the Expression of NPS and Its Receptor NPSR in the Anterior Cingulate Cortex and Hypothalamus

Abstract: Correspondence should be addressed to Jianqiao Fang; fangjianqiao7532@163.com and Junying Du;Objective. Electroacupuncture (EA) is reported effective in alleviating pain-related emotion; however, the underlying mechanism of its effects still needs to be elucidated. e NPS-NPSR system has been validated for the involvement in the modulation of analgesia and emotional behavior. Here, we aimed to investigate the role of the NPS-NPSR system in the anterior cingulate cortex (ACC), hypothalamus, and central amygdala … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Both animal and human studies have shown that EA can significantly improve chronic inflammatory pain and pain-induced disorders ( Lin et al, 2020 ). Our previous studies have demonstrated that EA relieved chronic inflammatory pain and pain-related anxiety by downregulating PKMzeta expression and upregulating the neuropeptide S (NPS)/NPSR system in the anterior cingulate cortex (ACC) ( Du et al, 2017 ; Du et al, 2020 ; Xu et al, 2020 ). However, the underlying mechanisms by which EA ameliorates chronic inflammatory pain-related anxiety has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Both animal and human studies have shown that EA can significantly improve chronic inflammatory pain and pain-induced disorders ( Lin et al, 2020 ). Our previous studies have demonstrated that EA relieved chronic inflammatory pain and pain-related anxiety by downregulating PKMzeta expression and upregulating the neuropeptide S (NPS)/NPSR system in the anterior cingulate cortex (ACC) ( Du et al, 2017 ; Du et al, 2020 ; Xu et al, 2020 ). However, the underlying mechanisms by which EA ameliorates chronic inflammatory pain-related anxiety has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The limbic system includes a wide range of interconnected brain regions that process and regulate cognitive function, sensory perception, memory, emotions, and affective motivation ( 68 ). Various limbic regions participate in pain processing circuits, including the hypothalamus ( 68 70 ), amygdala, and ACC ( 68 , 71 73 ).…”
Section: Preclinical Modelsmentioning
confidence: 99%
“…Encephalin and endorphin relieve pain-related emotions by upregulating the expression of neuropeptide S and its receptor in the anterior cingulate cortex and hypothalamus. 12 While the mechanism of acupuncture underlying PONV prevention has not been well elucidated, it may reduce PONV by releasing beta-endorphin or altering the transmission of serotonin. 13 Clinical trials and existing reviews indicate that AAA helps reduce the consumption of anaesthetic and analgesic agents, prevent PONV and relieve anxiety during surgery.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%